Upaya Peningkatan Resiliensi Masyarakat pada Masa Pandemi Covid-19 di Dusun Wage, Jawa Barat - Sri Wulandari, Khotimah; Taufik, Moh (LPkM Universitas Bakrie, 2022)
The Covid-19 pandemic had a comprehensive impact in all aspects of lives. This society service activities aim to increase resilience of society in Wage Hamlet RT 015 RW 005 Lebakwangi Village, Lebakwangi District, Kuningan Regency, West Java. The society from that location have serious experience that impacts in the aspects of educational, economic, health and religion. The online learning system caused some of students to go on strike to school, the income decreased up to 80%, susceptible to stress, anxiety and excessive fear, and religious activities were also forced to stop. The method used in this service was Participatory Action Research, namely by implementing various program activities which started with build a rapport with the society, determination of society service agendas, participatory mapping, identification of problems in society, planning or strategies planning, society organizing, implemented the change actions, reflection or evaluation, and then expanded the scale of action and support. In the educational aspects, there was Kejar Ilmu program as a place for tutoring and discussion. In the economic aspects, there was the creation of product brochures for online promotion through social medias. The health aspects there was Friday Sharing program and guidance & counselling service. The last aspect, the religious aspects, that was the implementation of weekly recitations and the preparation of material summaries for distribution online. In general, these society service activities go so well. It can be seen from the enthusiasm of the residents and have a lot of participants who participates in this activity.